Prevalence of feline coronavirus in two cat populations in Malaysia - Sharif, Saeed; Arshad, Siti Suri; Bejo, Mohd Hair; Omar, Abdul Rahman; Allaudin, Zeenathul Nazariah; Ismail, Mohd Afzal Hafidz (Elsevier, 2009)
The prevalence of feline coronavirus (FCoV) was studied in two catteries in Malaysia. Rectal swabs or faecal samples were collected from a total of 44 clinically healthy Persian purebred and mix-breed cats. RNA extracted from the faecal material was subjected to a reverse transcription-polymerase chain reaction (RT-PCR) using primers flanking for a conserved region of the virus genome. The overall prevalence of FCoV infection was 84% and the infection rate was higher in Persian purebred cats (96%) than mix-breed cats (70%). There was no significant association between the age or gender of tested cats and shedding the virus. This study is the first PCR-based survey for FCoV in Malaysia and showed the ubiquitous presence of FCoV in Malaysian cat colonies.